A living environment evaluation method based on the residentsâ€™ participation using the â€œliving environment mapâ€: development of improvement systems for the living environment by a residents' association through preparing the â€œliving environment mapâ€ part 1 - Kubota, T.; Miura, M.; Mizuno, A.; Inokuma, S. (2005)

(untitled)
The aim of this study is to develop improvement systems for the living environment by a residents' association through preparing the â€œLiving Environment Mapâ€. As the first stage of this study, this paper proposed a living environment evaluation method based on the residents' participation using the â€œLiving Environment Mapâ€ through a case study of Saitama City. The proposed method is composed of several field surveys, which are carried out by collaboration between the institute and the residentsâ€™ association. The method was characterized through the case study and in particular, residents' participation methods in each stage were considered.